Rapid Radiofrequency Field Mapping In Vivo Using Single-Shot STEAM MRI - Helms, Gunther (Wiley Subscription Services, Inc., A Wiley Company, 2008)
Higher field strengths entail less homogeneous RF fields. This may influence quantitative MRI and MRS. A method for rapidly mapping the RF field in the human head with minimal distortion was developed on the basis of a single-shot stimulated echo acquisition mode (STEAM) sequence. The flip angle of the second RF pulse in the STEAM preparation was set to 60° and 100° instead of 90°, inducing a flip angle-dependent signal change. A quadratic approximation of this trigonometric signal dependence together with a calibration accounting for slice excitation-related bias allowed for directly determining the RF field from the two measurements only. RF maps down to the level of the medulla could be obtained in less than 1 min and registered to anatomical volumes by means of the T(2)-weighted STEAM images. Flip angles between 75% and 125% of the nominal value were measured in line with other methods. Magn Reson Med 60:739–743, 2008. © 2008 Wiley-Liss, Inc.